The Characteristics of Green-synthesized Magnesium Oxide Nanoparticles (MgONPs) and their Biomedical Applications - Chandrasekaran, Rajkuberan; Patil, Sunita; Krishnan, Muthukumar; Kuca, Kamil (Mini Reviews in Medicinal Chemistry, 2023)
In the current epoch, noble metals/metal oxides with precise structures are needed to develop sustainable products to improve the welfare of human beings and the environment. Nanomaterials in the regime 1 -100 nm scale are a promising material for the research fraternities owing to their stupendous properties. The metallic/metal oxide nanoparticles (silver, gold, copper oxide, iron oxide, magnesium oxide) are gaining significant momentum and need to be extensively studied. Magnesium oxide nanoparticles (MgONPs) are a periclase, white hygroscopic material consisting of Mg2+ ions and O-2 ions in lattice arranged. These nanoparticles can be fabricated through physical, chemical and biological methods. The development of green synthesized MgONPs needs to be ascertained and explored its ultimate in medicine, health, cosmetics, environmental protection, chemical industries, and energy. Therefore, the present review manifests the green synthetic approaches of MgONPs and their impact on crystalline structure and shape. Further, we have provided the antibacterial and anticancer activities of MgONPs thoroughly reported in various kinds of literature. Overall, the unique MgONPs can be plausibly used as safe biomaterials in biomedical applications.
Keywords: green synthesis